非目的语环境下的汉语口语教学问题——以刚果布拉柴维尔市为例 - Freud Savinien Ngatseke Mampola (Sinolingua: Journal of Chinese Studies, 2024)
This study aims to explore the challenges of teaching Chinese oral language in a non-target language environment, using Congo (Brazzaville) as a case study, and to propose effective solutions. To achieve this goal, we employed a case study approach, conducting a detailed analysis of the current state of Chinese oral language teaching in Congo (Brazzaville). Through field interviews and classroom observations, we systematically identified the key challenges in teaching. The study found that the lack of consistency in setting teaching goals and training systems has limited the effectiveness of oral language instruction. Furthermore, the current approach is overly focused on grammar and structure, neglecting the development of oral communication skills. Based on these findings, we recommend enhancing the training of communicative skills in Chinese oral language teaching, while also incorporating listening comprehension to address the specific needs of a non-target language environment. The results of this study provide practical insights and theoretical support for improving Chinese oral language teaching in non-target language settings.